2017
DOI: 10.1117/1.jbo.22.6.066006
|View full text |Cite
|
Sign up to set email alerts
|

Fourier ptychographic microscopy using wavelength multiplexing

Abstract: Fourier ptychographic microscopy (FPM) is a recently developed technique stitching low-resolution images in Fourier domain to realize wide-field high-resolution imaging. However, the time-consuming process of image acquisition greatly narrows its applications in dynamic imaging. We report a wavelength multiplexing strategy to speed up the acquisition process of FPM several folds. A proof-of-concept system is built to verify its feasibility. Distinguished from many current multiplexing methods in Fourier domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…But the pixel size of a chromatic camera is usually larger than the monochrome camera, otherwise, the photon efficiency will be fairly low. Also, it needs to correct the error of color leakage [31]. The third approach is termed wavelengthmultiplexed FPM (WMFPM) scheme with a monochrome camera and multi-wavelength simultaneous illuminations [25,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…But the pixel size of a chromatic camera is usually larger than the monochrome camera, otherwise, the photon efficiency will be fairly low. Also, it needs to correct the error of color leakage [31]. The third approach is termed wavelengthmultiplexed FPM (WMFPM) scheme with a monochrome camera and multi-wavelength simultaneous illuminations [25,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…By illuminating multiple LEDs at a time for each captured image, it was shown that the incoherent superposition of the contribution of each LED could be separated within a novel reconstruction algorithm. After this demonstration, several strategies were proposed to choose alternative multiplexing LED patterns [128][129][130][131][132], and similar approaches were also later suggested for spectral multiplexing [79,133]. One of the fastest FP systems to date was demonstrated using this multiplexing concept [26].…”
Section: High-speed Fourier Ptychographymentioning
confidence: 99%
“…However, large overlapped and sequential acquisitions are required to synthesize the FPM data, which restricts conventional FPM to static and thin samples. To solve this problem, different techniques such as sparse sampling [3,4] and adaptive sampling method [5,6] with different regularizations [7] are applied to greatly reduce the image numbers required for FPM reconstruction. In the meantime, other modeling methods such as ptychographic tomography [8] are proposed to extend the method to thick samples.…”
Section: Sbp Limitmentioning
confidence: 99%